The BFI companion to crime - Hardy, Phil, 1945-2014.; British Film Institute (Berkeley : University of California Press, 1997)
Robbers, gangsters, murderers, and criminals of every description have long been a staple of popular entertainment. Movies are no exception, and film buffs and scholars alike now have a complete guide to the vast array of films that make up the fascinating world of crime cinema. The BFI Companion to Crime offers detailed information on the sub-genres and motifs of movies dealing with criminals and their behavior: prison dramas, heist stories, kidnappings, the exploits of serial killers, juvenile delinquents, and hired guns. Phil Hardy also includes articles on the historical and social background of crime movies. The Mafia, the Japanese yakuza, the FBI, and the underworld of union rackets, prostitution, and drugs are some of the topics covered. Fictional characters such as Sherlock Holmes, Inspector Maigret, Philip Marlow, and Pretty Boy Floyd appear in these pages, along with the literary sources of many crime films. The works of Graham Greene, Dashiell Hammett, Mickey Spillane, and Eric Ambler are among those featured. Abundantly illustrated with more than 500 photographs, this is the book for film enthusiasts and anyone interested in the crime genre.
Keywords: Detective and mystery films -- History and criticism; Gangster films -- History and criticism; Police films -- History and criticism; Detective and mystery films -- Catalogs; Gangster films -- Catalogs; Police films -- Catalogs; Películas policiacas; Cine